PROPIEDADES PSICOMÉTRICAS DE LA ESCALA DE AFRONTAMIENTO AL ESTRÉSENFOCADA A LA EMOCIÓN EN PACIENTES HOSPITALIZADAS DEL INMP – 2024 - Silva Dominguez, Daniel Sergio (2025)
Introduction. Emotional coping is essential in pregnant women with complications. Objective. To analyze the psychometric properties of the Brief Coping Strategies Inventory (CSI-FV) in hospitalized patients at the Instituto Nacional Materno Perinatal. Materials and Methods. Psychometric instrumental study using secondary data from women over 18 years old without a history of mental disorders, obtained from two previous investigations. The first sample (n=208) was used to describe the items and perform confirmatory factor analysis (CFA) of the original model, as well as exploratory factor analysis (EFA) of five alternative models: four-, three-, and two-dimensional structures, and two unidimensional models—six factorial structures in total. Reliability (Cronbach’s alpha, ordinal alpha, and omega) and validity (CFI, TLI, SRMR, RMSEA) were assessed. A second sample (n=440), composed of 220 patients diagnosed with preeclampsia or hypertension and 220 without such diagnoses, was used to assess measurement invariance and convergent validity with the Generalized Anxiety Disorder Scale (GAD-7). Results. The two-factor model showed the best psychometric indicators. Factor 1 (emotional engagement) showed alpha=0.72; ordinal alpha=0.75; omega=0.78, and Factor 2 (emotional avoidance) showed alpha=0.80; ordinal alpha=0.83; omega=0.84. Good fit indices were obtained: CFI=0.986; TLI=0.974; SRMR=0.064; RMSEA= 0.078 (90% CI: 0.054–0.097). Measurement invariance was weak between groups (M1–M2=0.003; M2–M3=0.007; M3–M4=0.033). A direct and significant correlation was found between Factor 2 and anxiety (rho=0.325; p<0.001), and an inverse significant correlation with Factor 1 (rho=–0.162; p<0.050). Conclusion: The six-item, two-factor CSI-FV shows adequate validity, reliability, and clinical sensitivity to assess emotional coping strategies in hospitalized patients.